Culture and Successful Eradication of Helicobacter pylori from Heterotopic Gastric Mucosa - Wüppenhorst, N.; Viebahn, B.; Theile, A.; Radü, H. J.; Kist, M. (Zeitschrift für Gastroenterologie, 2012)
Helicobacter pylori colonizes the gastric mucosa of humans and can cause chronic gastritis, peptic ulcer disease, gastric cancer or mucosa-associated-lymphoid tissue (MALT) lymphoma. Here, we report the case of a 61-year-old male patient who presented with tickle of the throat, globus sensation and heartburn. In an esophagogastroduodenoscopy subpharyngeal localized heterotopic gastric mucosa (HGM), reflux esophagitis and a chronic gastritis were diagnosed. HGM and stomach were H. pylori positive as proven by culture and histopathological examination. After eradication therapy with a proton pump inhibitor (PPI), amoxicillin and clarithromycin followed by PPI treatment, the patient reported clinical improvement and the histopathological changes in the HGM due to H. pylori infection improved, too. This case report demonstrates that culture and susceptibility testing of H. pylori using established protocols succeeds not only from tissue samples of the stomach but also from heterotopic gastric mucosa. Eradication therapy may not only improve typical H. pylori associated discomforts of the stomach but also extragastric signs and symptoms of H. pylori infection.
Keywords: Key words; Helicobacter pylori; heterotopic gastric mucosa; susceptibility testing; eradication therapy